Usual pathology at an unusual site - pleomorphic adenoma of parapharyngeal space: a rare case report - Chauhan, Pankaj; Khanoria, Rita; Sharma, Disha; Guleria, Trilok C. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The parapharyngeal space is an inverted triangular pyramid. Parapharyngeal space masses account for 0.5% of all head and neck tumours and the majority is benign. Minor salivary gland tumour is a rare entity. A 75 years old female presented with a mass left side soft palate, per operatively mass of size about 6×3 cm was deeply extending to left parapharyngeal space and excised through transoral approach which came out to be pleomorphic adenoma of minor salivary gland on histopathological examination. Although external approach should be preferred due to important structure in vicinity but transoral approach can be used in selective cases.